Interaction of language, auditory and memory brain networks in auditory verbal hallucinations. (January 2017) - Ćurčić-Blake, Branislava; Ford, Judith M.; Hubl, Daniela; Orlov, Natasza D.; Sommer, Iris E.; Waters, Flavie; Allen, Paul; Jardri, Renaud; Woodruff, Peter W.; David, Olivier; Mulert, Christoph; Woodward, Todd S.; et al.
Highlights: The language, auditory and memory/limbic networks are of particular relevance for auditory verbal hallucinations. An increased interaction among the auditory-language and striatal brain regions occurs while patients hallucinate. Fronto-temporal connections are often altered in AVH individuals, but there is no consensus regarding increase or decrease. Connections of the interhemispheric auditory pathway are stronger for first episode patients, but they are weaker in chronic patients. The majority of studies support hybrid AVH hypotheses in which all three networks and the striatal network are involved. Abstract: Auditory verbal hallucinations (AVH) occur in psychotic disorders, but also as a symptom of other conditions and even in healthy people. Several current theories on the origin of AVH converge, with neuroimaging studies suggesting that the language, auditory and memory/limbic networks are of particular relevance. However, reconciliation of these theories with experimental evidence is missing. We review 50 studies investigating functional (EEG and fMRI) and anatomic (diffusion tensor imaging) connectivity in these networks, and explore the evidence supporting abnormal connectivity in these networks associated with AVH. We distinguish between functional connectivity during an actual hallucination experience (symptom capture) and functional connectivity during either the resting state or a task comparing individuals who hallucinate with those who do not (symptom association studies). Symptom capture studies clearly reveal a pattern of increased coupling among the auditory, language and striatal regions. Anatomical and symptom association functional studies suggest that the interhemispheric connectivity between posterior auditory regions may depend on the phase of illness, with increases in non-psychotic individuals and first episode patients and decreases in chronic patients. Leading hypotheses involving concepts as unstable memories, source monitoring, top-down attention, and hybrid models of hallucinations are supported in part by the published connectivity data, although several caveats and inconsistencies remain. Specifically, possible changes in fronto-temporal connectivity are still under debate. Precise hypotheses concerning the directionality of connections deduced from current theoretical approaches should be tested using experimental approaches that allow for discrimination of competing hypotheses.